Women's peacebuilding iniatives in the Benue Valley, Nigeria : gender, fundamental human needs and conflict resolution - Agberagba, John Tavershima (Irish School of Ecumenics, 2014)
In this research, I investigate and provide a multi-disciplinary scholarly analysis of four grassroots groups of women peacebuilding in the multi-communal Benue Valley, Nigeria (BVN): to offer analysis of the causes of violent conflicts in the region with an emphasis on understanding the deprivation of human needs as a vital cause and to show how the women's peacebuilding initiatives meet some of the unmet frustrated needs.
Keywords: Religions, Peace Studies and Theology, Ph.D.; Ph.D. Trinity College Dublin